2003
DOI: 10.1207/s1532480xads0702_6
|View full text |Cite
|
Sign up to set email alerts
|

What Exactly Is a Youth Development Program? Answers From Research and Practice

Abstract: Approaches to positive youth development: A view of the issues. In R. K. Silbereisen & R. M. Lerner (Eds.), Approaches to positive youth development (pp. 3-30). London, England: Sage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
406
0
27

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(438 citation statements)
references
References 4 publications
5
406
0
27
Order By: Relevance
“…Current theories of youth development emphasize that positive or healthy psychological and social functioning does not involve only the absence of risk/problem behaviors, but also include the presence of characteristics of successful and adaptive behavior. In the 'positive youth development' (PYD) perspective (Lerner, 2005), the presence of psychosocially and physically healthy change is indexed not by decreases in negative behaviors (eg substance use and abuse, bullying, or depression) but by increases in attributes indicative of thriving, such as the 'five Cs' of PYD: Competence, Confidence, Connection, Character, and Caring (Lerner et al, 2000Eccles and Gootman, 2002;Roth and Brooks-Gunn, 2003). These 'Cs' have been found to be the outcomes of functionally and developmentally appropriate (adaptive) interactions between the young person and his/her social ecology; importantly, these attributes appear to be inversely related to indicators of both internalizing and externalizing risk/ problem behaviors (Gestsdottir and Lerner, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Current theories of youth development emphasize that positive or healthy psychological and social functioning does not involve only the absence of risk/problem behaviors, but also include the presence of characteristics of successful and adaptive behavior. In the 'positive youth development' (PYD) perspective (Lerner, 2005), the presence of psychosocially and physically healthy change is indexed not by decreases in negative behaviors (eg substance use and abuse, bullying, or depression) but by increases in attributes indicative of thriving, such as the 'five Cs' of PYD: Competence, Confidence, Connection, Character, and Caring (Lerner et al, 2000Eccles and Gootman, 2002;Roth and Brooks-Gunn, 2003). These 'Cs' have been found to be the outcomes of functionally and developmentally appropriate (adaptive) interactions between the young person and his/her social ecology; importantly, these attributes appear to be inversely related to indicators of both internalizing and externalizing risk/ problem behaviors (Gestsdottir and Lerner, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These figures clearly revealed that more effort is needed in positive youth development research, especially for the development of sound psychometric measures. Roth and Brooks-Gunn (2003) highlighted the importance of valid and reliable measurement tools, as it tell us why certain programs are successful in promoting healthy development among participants' lives. The availability of positive youth development instruments provides a better understanding of how a program positively impacts youths, and thereby improving the quality of programs in the future (National Research Council, 2002;Roth et al, 1998).…”
mentioning
confidence: 99%
“…Entretanto, não são apenas as condições estabelecidas pelos contextos, mas o tempo que o jovem despende com adultos cuidadores e com pares, em atividades que reforçam valores associados à saúde e ao bem-estar comum, que asseguram seu sucesso escolar, e garantem o desenvolvimento de valores e comportamentos relativos à consciência social, liderança, solidariedade e valorização da diversidade (Benson, 2003;Roth & Brooks-Guhn, 2003;Theokas et al, 2005).…”
Section: Tendências Atuais: a Visão Do Desenvolvimento Positivounclassified
“…Os estudos atuais buscam apresentar dados que sirvam de base para programas dirigidos aos adolescentes, já que é nesta fase que um grande potencial pode ser desenvolvido, preparando-os para enfrentar melhor os desafios e atuar no mundo adulto (Larson, Wilson & Mortimer, 2002;Roth & Brooks-Guhn, 2003;Smetana, Campione-Barr & Metzer, 2006).…”
unclassified